Architecture and Religiosity: Integration of Local Culture and Islam in the Tomb of Dewi Sekardadu in Gresik, East Java - Lutfiyah, Siti Khumairotul (PT. Student Rihlah Indonesia, 2025)
Dewi Sekardadu was the biological mother of Sunan Giri, one of the members of the Walisongo. This study examines the integration of local culture and Islam in the architecture of the Dewi Sekardadu Tomb in Gresik, East Java, which serves as a significant representation of cultural acculturation in Indonesia. The importance of this research lies in its in-depth understanding of how architectural elements reflect religious values and local identity. The aim of this study is to identify and analyze the architectural elements and symbolism contained within the tomb, as well as their relationship to the religious practices of the local community. The methodology employed is a descriptive-qualitative approach with an interactive analysis model, which includes data collection through observation, interviews, and documentation, as well as data credibility testing through triangulation and member checks. The results obtained are: (1) the architectural style of the Dewi Sekardadu Tomb in Gresik, East Java, represents local architecture that emphasizes symbolism, and (2) the expression of local wisdom in the architecture of the Dewi Sekardadu Tomb is evident in the cungkup (roofed structure), the layout of the tomb, gapura (gate), jirat and gravestone, pendopo (pavilion), and floral ornaments that depict local culture.